Analysis of heat exchanger in an air handling unit – A case study - Borowski Marek (EDP Sciences, 2021)
Ventilation plays an important role in providing comfortable conditions for users and is also one of the most energy-consuming systems in the building. Due to successive regulations aimed at reducing the energy load of buildings towards zero-energy buildings, energy recovery systems in air handling units have become an indispensable element. The high effectiveness of the entire system guarantees a reduction in energy demand. At very low or very high external temperatures, appropriate comfort conditions are provided by additional heaters or coolers. The subject of the paper is a ventilation system in a hotel located in southern Poland. The building is a faithful reconstruction of the historical saltworks adapted for the needs of the hotel. The air handling unit equipped with a rotary exchanger supplies air to hotel rooms located on two floors. The analysis includes the effectiveness of the air-handling unit operation under various external conditions, as well as the temperature changes during heat exchange. The results show the actual operation of the air-handling unit, which is particularly important in terms of reducing the energy consumption of the hotel.